Post-processing of 3D printed thermoplastic CFRP composites using cryogenic machining. (August 2021) - Cococcetta, Nicholas; Jahan, Muhammad P.; Schoop, Julius; Ma, Jianfeng; Pearl, David; Hassan, Mahmudul
Abstract: Additive manufacturing (AM) or three-dimensional (3D) printing allows manufacturing of parts of complex shapes using carbon fiber reinforced polymer (CFRP) composites. However, in many cases, the parts fabricated by 3D printing suffer from poor surface quality and dimensional accuracy, requiring extensive post-processing. This research aims at improving the dimensional accuracy and surface finish of 3D printed CFRP composites by analyzing the effectiveness of three sustainable machining practices: dry, minimum quantity lubrication (MQL), and cryogenic machining, as post-processing techniques for 3D printed CFRP composites. This study specifically investigates effects of printing and machining parameters and cooling/lubricating conditions on the machining performance, i.e., burr formation, surface finish, cutting forces, and tool wear during edge and slot milling of 3D printed thermoplastic CFRP composites. Among three sustainable machining processes, cryogenic machining significantly reduced burr formation and tool wear, and improved surface finish irrespective of the fiber orientation and machining conditions. The application of MQL at the tool-workpiece interface was found to be effective in reducing tool wear, surface roughness, and burr formation to some extent compared to dry machining. However, MQL process was not able to completely eliminate burr formation for most of the machining conditions. Cryogenic machining caused the highest cutting forces due to the increased surface and sub-surface hardness of the workpiece caused by application of liquid nitrogen; however, no adverse effect of increased cutting forces was observed. This study finds that cryogenic machining is able to completely eliminate or reduce burrs by 90% and bring down the surface roughness (Rq) from >10 μm to about 1 μm, thus making it a suitable post-process technique for 3D printed CFRP composites.